TEACHING GEOMETRY WITHOUT USING CALCULATORS: AN EXPERIMENTAL CASE ON GRADE-9 THAI LEARNERS (Isagoge - Journal of Humanities and Social Sciences, 2021)
Should we solve geometry problems using calculators? This study identified the effect of using (and not using) calculators during calculations on geometry problems sets, as well as the perceived impact on the use of calculators based on students’, parents’ and school administrators’ perception in a school in Bangkok, Thailand. This study combined both qualitative (survey and interview) and quantitative techniques (experiment) to address the research problem. Findings revealed that the performance of students who used calculators in the experiment did not significantly differ with those who did not which suggests that non-usage of calculators will not affect solving geometry problems, at least in the context of Thai Math education. Further, survey showed that students only used calculators ‘sometimes’ outside class and gave diverse responses when asked why. Interview with parents, students and administrators showed transcript extracts mostly on their agreement to use calculators in geometry class citing the convenience and speed of doing problems but implied a negative impact on their academic performance in math problems in the real world. This study could provide a baseline information on the use of calculators in the teaching of Math lessons for other nationalities.
Keywords: Mathematics; Geometry; Effect of Usage or Non-usage of Calculator